Preparation method and application of NiS2 / nitrogen-doped carbon composite material constructed by derivative confinement of coordination compound
The NiS2/nitrogen doped carbon composite material is constructed through the limited domain of the coordination compound, which solves the problems of low conductivity, easy agglomeration and unstable structure in sodium ion batteries, and achieves the improvement of high cycle stability and rate performance, which is suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411850182.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The existing NiS2 materials have problems such as low conductivity, easy agglomeration, and unstable structural structure in sodium ion batteries, resulting in poor cycle stability and rate performance, making it difficult to achieve commercial application.
NiS2/nitrogen doped carbon composite material is constructed by the coordination compound derivatization domain, Ni-HMT precursor is prepared by mechanochemical method, and NiS2 particles uniformly distributed on the nitrogen-doped carbon framework are generated through heat treatment and vapor phase sulfurization to avoid material agglomeration and volume changes.
It improves the cycle stability and rate performance of the material, enhances chemical affinity and conductivity, and is suitable for large-scale industrial production.
Smart Images

Figure CN119695106A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a preparation method and application of a coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material. Background Art
[0003] At present, although lithium-ion batteries have been widely used in the commercial field, due to the limited lithium resources and the continuous rise in prices, relying solely on lithium-ion batteries can no longer meet the needs of large-scale development in the future. In this context, sodium-ion batteries are regarded as a powerful alternative to lithium-ion batteries due to their abundant sodium resources, lower costs, and similar working mechanisms to lithium-ion batteries. Sodium-ion batteries have broad prospects for large-scale application and are expected to play an important role in the future energy field.
[0004] The negative electrode material is one of the important components of sodium-ion batteries and affects the overall performance of sodium-ion batteries. Among the many existing negative electrode materials, hard carbon has become the mainstream choice due to its stable structure and good electrochemical performance. However, the high preparation cost and limited sodium storage capacity of hard carbon limit the improvement of the energy density of sodium-ion batteries. Transition metal sulfides that rely on conversion reactions, especially NiS2, have a high theoretical specific capacity (870mAh g -1 ), which can effectively improve the energy density of sodium batteries and show certain competitive advantages in the field of sodium ion battery negative electrode materials. However, this type of material still has problems such as low ion conductivity, easy agglomeration, and easy structural collapse during the cycle, resulting in unsatisfactory actual cycle stability and rate performance, poor electrochemical performance, and hindering its commercial application.
[0005] At present, researchers have adopted a variety of strategies to solve the above problems: construct heterojunctions, design nanostructures, and carbon-coat materials to improve the overall performance of materials. For example, patent CN113314715B discloses a nickel sulfide composite material and its preparation method and application. By compounding NiS2 particles with carbon materials, the material structure is stabilized, the volume change is slowed down, and it is not easy to break during the cycle. First, nickel acetate and surfactant are dissolved in alcohol for 12 to 60 hours of solvent thermal reaction to obtain a precursor; then, the precursor is dispersed in a tris (hydroxymethyl) aminomethane solution, dopamine hydrochloride is added, and the reaction is filtered to obtain a precipitate to obtain a coating, and the coating is mixed with sulfur and calcined to obtain the nickel sulfide composite material. However, in this technical solution, long-term hydrothermal reaction will lead to an increase in energy consumption during the reaction process, and the use of organic solvents will also cause harm to the environment and human body. For example, patent CN116470029A provides a cobalt tetrasulfide @ nickel disulfide / carbon composite material and its preparation method and application in sodium ion batteries. NiS2 is combined with other transition metal sulfides to construct a heterojunction to make up for the low conductivity and slow ion diffusion kinetics of single metal sulfide NiS2. Cobalt source, sulfur source, NH4F and urea are mixed in a certain molar ratio for a 10-14h hydrothermal reaction to obtain a CoS nanosphere precursor; the CoS nanosphere precursor, organic ligand, surfactant and nickel source are then mixed in a solvent for a 10-14h hydrothermal reaction to obtain an intermediate CoS@Ni-MOFs nanosphere; finally, the intermediate CoS@Ni-MOFs nanosphere is mixed with sulfur powder and calcined under a protective atmosphere to obtain a Co3S4@NiS2 / C composite material. However, different sulfides have different physical and chemical properties (anisotropy) in different crystal plane directions. The heterojunction formed by multiple sulfides will aggravate this anisotropy during the cycle process. The aggravated anisotropy will lead to a decrease in the interface bonding degree of the heterojunction, affecting the conductivity of the material and ultimately limiting the cycle life of the material. In addition, multiple hydrothermal reactions combined with vapor phase sulfidization and the compounding of multiple metal salts will lead to an increase in raw material costs, making it difficult to achieve large-scale production in industry.
[0006] In summary, although the above methods can partially solve the problems of conductivity, ion diffusion kinetics, structural stability, etc. of NiS2 materials, the final product does not have a long cycle life. At the same time, the use of hydrothermal and various organic solvents will increase the energy loss, time cost, environmental problems of the preparation, and is not suitable for large-scale use in the commercial preparation process of battery electrode materials. Summary of the invention
[0007] In view of the above technical problems, the present invention provides a preparation method and application of a coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material. The preparation method of the present invention is simple, avoids long-term reaction and reduces the use of organic solvents. The product limits NiS2 particles through the carbon skeleton generated by in-situ conversion. The carbon skeleton plays a confining role so that NiS2 particles are tightly embedded in the carbon skeleton, nano-materials are formed and agglomeration of materials is avoided, and the volume change during the charge and discharge process is alleviated. At the same time, it has better binding than externally introduced carbon; heteroatoms (nitrogen) are introduced into the carbon skeleton to enhance the chemical affinity of the material; single metal sulfide NiS2 is used as the active material to avoid the construction of heterojunctions, and the conductivity of the electrode material is prevented from decreasing during the cycle due to the decrease in the degree of binding at the heterojunction interface, thereby improving the cycle life of the material. This composite material has a higher actual capacity and better cycle stability and rate performance when used as a negative electrode material for sodium ion batteries.
[0008] The specific technical scheme of the present invention is: a preparation method of a coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material, comprising the following steps:
[0009] (1) Nickel salt and organic ligand hexamethylenetetramine are placed in a ball mill, and a coordination compound Ni-HMT precursor is obtained through a mechanochemical reaction and washing.
[0010] (2) The Ni-HMT precursor is pyrolyzed under an inert protective atmosphere to obtain an intermediate product.
[0011] (3) The intermediate product is heat-treated with a sulfur source under an inert protective atmosphere to obtain a NiS2 / nitrogen-doped carbon composite material having a nitrogen-doped carbon skeleton and uniformly distributed NiS2 particles.
[0012] The coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material obtained by the method of the present invention has the following advantages: (1) The NiS2 / nitrogen-doped carbon composite material prepared by the present invention retains the precursor channel and skeleton structure, and the post-treated material has high porosity and large specific surface area, providing a channel for sodium ion shuttle; (2) Compared with the introduction of carbon by other means, the nitrogen-doped carbon generated by the in-situ conversion of the coordination compound can be tightly combined with the NiS2 particles, effectively slowing down the volume change caused by the insertion / extraction of sodium ions, enhancing the material's cyclic stability, and the incorporation of nitrogen elements in the carbon skeleton improves the material's chemical affinity, provides more active sites, and improves the overall conductivity of the composite material; (3) When the composite material is used as the negative electrode of a sodium ion battery, its composite structure can effectively promote the full infiltration of the electrolyte and the rapid migration of sodium ions, and has good cycle stability and rate.
[0013] In addition, the present invention adopts a mechanochemical method to prepare a Ni-HMT precursor, and then obtains a NiS2 / nitrogen-doped carbon composite material by heat treatment and vapor phase sulfurization. The synthesis method using a mechanochemical method as a precursor can avoid the shortcomings of traditional hydrothermal method, high-temperature solid phase method, vapor phase deposition method, etc., and reduce the problems of solvents, large amounts of energy consumption, and long time required in the reaction process. The preparation process is simple, the reaction temperature is low, it is green and environmentally friendly, and the yield is high, and it can be applied to large-scale industrial production.
[0014] Preferably, the mechanochemical reaction (ball milling) of the present invention includes two schemes:
[0015] Scheme A: A one-step ball milling method is adopted: the mass ratio of the total mass of the nickel salt and the organic ligand hexamethylenetetramine to the ball milling beads (medium ball milling beads, diameter 8-12 mm) is 1:(10-40); the time of the mechanochemical reaction is 1-8 hours, and the rotation speed is 300-600 rpm.
[0016] In the entire preparation step of the ball milling process using the above scheme A, the main reaction process is as follows: First, during the ball milling process, the reaction raw material block is broken into small particles or powders under the strong mechanical force of the large ball milling beads. When the small ball milling beads collide with each other, the contact surface generates high temperature, and the organic ligand molecule HMT absorbs energy to break the molecular bond, and the broken molecular bond is coordinated and chelated with the Ni metal ion to form a Ni-HMT complex; then the obtained Ni-HMT precursor is carbonized under a protective atmosphere, and the organic component in the complex is thermally decomposed to form a stable carbon skeleton, and the metal ion component is converted into Ni single metal under carbon thermal reduction; finally, the process of gas phase sulfurization is carried out, and the sulfur source gradually sublimates into sulfur vapor during the heating process, and the Ni metal reacts with the sulfur vapor to generate NiS2, and the residual sulfur vapor is removed with the air flow. The obtained nitrogen-doped carbon skeleton surface and internal distribution of NiS2 particles is the NiS2 / nitrogen-doped carbon composite material.
[0017] Scheme B: Three-step ball milling method: including the following stages:
[0018] The first stage: using large ball milling beads as the main method to break up the bulky nickel salt and organic ligand hexamethylenetetramine particles; the mass ratio of the total mass of nickel salt and organic ligand hexamethylenetetramine to the mass ratio of ball milling beads is 1:(10-40), the diameter of large ball milling beads is 15-25 mm, the diameter of small ball milling beads is 3-7 mm, the mass ratio of large and small ball milling beads is (7.5:2.5)-(8.5:1.5), the ball milling time is 1-2 hours, and the rotation speed is 400-600 rpm;
[0019] The second stage: without changing the ball-to-material ratio, some large ball milling beads are replaced with small ball milling beads of the same mass, and the crushed nickel salt and hexamethylenetetramine particles are mixed to further refine and promote the reaction; the mass ratio of large and small ball milling beads is (2.5:7.5) to (3.5:6.5), the ball milling time is 2 to 4 hours, and the rotation speed is 300 to 500 rpm;
[0020] The third stage: adding a grinding aid and dispersant, continuing ball milling, and after the reaction is completed, taking out the product, washing it with a detergent, and centrifuging it to obtain the coordination compound Ni-HMT precursor; the grinding aid and dispersant are isopropanol, anhydrous ethanol or ethylene glycol, the ball milling speed is 200-400rpm, and the ball milling time is 1-3h.
[0021] In the entire preparation step of the ball milling process of the above-mentioned scheme B, the main reaction process is as follows: large material particles and large ball milling beads are placed in a ball mill together, and the large raw material particles are broken into smaller particles by the strong mechanical force of the large ball milling beads at a high speed; when the size of the raw material particles is broken to approximately the same size, most of the large ball milling beads are replaced with small ball milling beads, and the ball milling is performed again to further mix and refine the broken material particles. During the ball milling process, the reaction mainly occurs on the surface of the ball milling beads. When the ball milling beads collide with each other, the contact surface generates high temperature, and the organic ligand molecule HMT absorbs energy. The amount of organic ligands breaks the valence bonds, and the broken valence bonds are coordinated and chelated with Ni metal ions to form Ni-HMT complexes. When the mass of the ball milling beads is the same, the specific surface area of the small ball milling beads is larger, and the materials are more likely to react with each other, thus achieving synthesis between the reaction materials; the grinding aid dispersant is subsequently added and the ball milling is repeated. Due to the presence of the grinding aid dispersant, even if there is no ball milling effect, it is not easy for the nanoparticles to aggregate (agglomerate). The sample particles can stably exist in a state of high surface energy, maintain a small particle state, and easily obtain nanoparticles in the subsequent heat treatment process. Compared with Scheme A, the material particles obtained by Scheme B are smaller in nanometer size and do not have agglomeration.
[0022] Preferably, in step (1), the molar ratio of the nickel salt to hexamethylenetetramine is (1-3):(0.5-3).
[0023] In order to obtain a more suitable Ni-HMT precursor, the molar ratio of nickel salt to organic ligand in the present invention is very critical. If the content of organic ligand is too much compared to nickel salt, the final carbon content in the material will be too much, resulting in a decrease in performance. If the content of nickel salt is too much compared to organic ligand, the nickel salt cannot be completely complexed by organic ligand, and obvious large particles will appear after subsequent carbonization, causing the material to expand and break during the cycle, resulting in a decrease in cycle stability. Finally, the present invention controls the molar ratio of nickel salt to organic ligand HMT within the above range, and the comprehensive effect is the best.
[0024] Preferably, in step (2), the pyrolysis temperature is 400-800°C, and the heating rate is 1-8°C·min -1 , the insulation time is 1 to 5 hours.
[0025] During the pyrolysis process, the structure and state of the intermediate after pyrolysis have a significant impact on the subsequent products, so the pyrolysis process is very critical. If the pyrolysis temperature is too low, the reaction rate will be reduced, the reaction time will be increased, and the material may not be completely reacted within the specified time to generate a mixture of reactants and intermediates; if the pyrolysis temperature is too high, it may cause excessive carbonization of the surface of the material, and even burn damage and deformation, which will affect the carbonization effect and cause excessive energy loss; the heating rate during pyrolysis also has a significant impact on the intermediate. If the heating rate is too fast, the temperature difference between the inside and outside of the precursor is too large, the outside part has been pyrolyzed, but the inside has not changed, which will cause the structure and morphology of the material to be destroyed, and the uniformity of the product will be reduced. If the heating rate is too slow, the reaction time at the same temperature needs to be extended, affecting the overall production efficiency. The present invention controls the temperature for pyrolysis within the above range, and the intermediate product obtained is the best.
[0026] Preferably, in step (3), the mass ratio of the intermediate product to the sulfur source is 1:(2-8).
[0027] During the gas phase vulcanization process, the intermediate product and the sulfur source are heat treated under a protective atmosphere. In order to obtain the NiS2 / nitrogen-doped carbon composite material with the most ideal performance and the purest physical phase, the mass ratio of the intermediate product to the sulfur source is controlled at 1: (2-8). If the ratio of the intermediate product to the sulfur source is too low, there will be excess sulfur vapor during the reaction, which will be attached to the product in the form of physical adsorption. A large amount of sulfur will cover a part of the reaction sites when attached to the product, resulting in a decrease in the electrochemical performance of the product. At the same time, a large amount of sulfur source will cause waste of resources, increase in cost and environmental pollution; if the ratio of the intermediate product to the sulfur source is too high, the reaction cannot be fully carried out, and the pure physical phase cannot be obtained, which reduces the reaction rate.
[0028] Preferably, in step (1), the nickel salt is any one of nickel chloride, nickel acetate, nickel sulfate or nickel nitrate.
[0029] Preferably, in step (1), the washing detergent is anhydrous ethanol, ethylene glycol, deionized water or N,N-dimethylformamide.
[0030] Preferably, in step (2), the protective atmosphere is argon or nitrogen.
[0031] Preferably, in step (3), the sulfur source is sulfur powder, L-cysteine, thiourea or thioacetamide.
[0032] Preferably, in step (3), the heat treatment temperature is 200-600° C.; and the inert protective atmosphere is nitrogen or argon.
[0033] Preferably, in step (3), the carbon skeleton in the NiS2 / nitrogen-doped carbon composite material having a nitrogen-doped carbon skeleton and uniformly distributed NiS2 particles has pores with a pore size of 2 to 8 μm, and the NiS2 particles are confinedly distributed in the nitrogen-doped carbon skeleton with a particle size of 50 to 100 nm.
[0034] The present invention also provides the use of the coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material obtained by the above preparation method as a negative electrode material for a sodium ion battery.
[0035] Compared with the prior art, the beneficial effects of the present invention are:
[0036] (1) The present invention obtains the precursor of Ni-HNT by a relatively simple mechanical ball milling and washing method, which effectively avoids the problems of traditional hydrothermal method, high temperature solid phase method, vapor phase deposition method, etc., which require a lot of energy and take a long time to synthesize materials. The synthesis process is simple, the reaction temperature is low, the yield is high, and it can be used for large-scale industrial production.
[0037] (2) Compared with carbon introduced by other means, the nitrogen-doped carbon generated by the in-situ conversion of the coordination compound in the present invention can be tightly combined with the NiS2 particles. The carbon layer plays a confining role, avoiding agglomeration between NiS2 nanoparticles and effectively alleviating the volume change caused by the insertion and extraction of sodium ions, avoiding the breakage and decomposition of the material, and enhancing the cyclic stability of the material.
[0038] (3) In the method of the present invention, heteroatoms (nitrogen) are used to modify the carbon material, thereby improving the chemical affinity of the material and providing more active sites, thereby improving the overall conductivity of the composite material.
[0039] (4) The NiS2 / nitrogen-doped carbon composite material prepared by the present invention obtains high porosity and large specific surface area after post-treatment, which effectively alleviates the volume effect of the electrode material during the sodium insertion and deinsertion process.
[0040] (5) The present invention provides two ball milling processes, which generate a conductive carbon substrate through in-situ conversion to improve the conductivity of the material, alleviate the volume change during the charge and discharge process, and reduce the agglomeration of the material while nano-sizing the material. The composite material has a higher capacity and a longer cycle life when used as a negative electrode material for a sodium ion battery. Among them, Scheme B performs multiple ball millings by changing the ball milling parameters and adding a grinding aid to better reduce the agglomeration of the material, and after subsequent treatment, the obtained NiS2 / nitrogen-doped carbon material has a better morphology and a smaller particle size.
[0041] (6) The NiS2 / nitrogen-doped carbon composite material prepared by the method of the present invention exhibits good electrochemical performance as the negative electrode of sodium ion batteries at a wide potential range of 0.01-3V, and the actual capacity can be maintained at 670mAh g -1 , and the rate can return to the initial capacity after cycling. NiS2 / nitrogen-doped carbon materials are prepared by high-energy ball milling. The products are high in purity, easy to prepare, and have good stability, making them suitable for large-scale use in the commercial preparation of battery electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is the X-ray powder diffraction pattern of the Ni-HMT precursor prepared in Example 1 of the present invention;
[0043] Figure 2 is a scanning electron microscope image of the intermediate product prepared in Example 2 of the present invention;
[0044] Figure 3 is a scanning electron microscope image of the final product prepared in Example 1 of the present invention;
[0045] Figure 4 is a scanning electron microscope image of the final product prepared in Example 6 of the present invention;
[0046] Figure 5 is the X-ray powder diffraction pattern of the final product prepared in Example 4 of the present invention;
[0047] Figure 6 The final product prepared in Example 1 of the present invention is 1Ag -1 Cycle performance under
[0048] Figure 7 The rate diagram of the final product prepared in Example 1 of the present invention at different current densities. DETAILED DESCRIPTION
[0049] The present invention is further specifically described below by way of examples, but the present invention is not limited to the following examples.
[0050] Example 1
[0051] (1) Add 2 mmol of nickel nitrate and 2 mmol of hexamethylenetetramine into a ball mill;
[0052] (2) Add 30 g of agate balls with a diameter of 10 mm into the ball mill;
[0053] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and performing ball milling for 6 hours at a rotation speed of 400 rpm. After the ball milling is completed, a mixed product is obtained;
[0054] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with anhydrous ethanol to obtain a Ni-HMT precursor.
[0055] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under argon atmosphere protection and heated at 2 °C min -1 The temperature was raised to 600℃ and pyrolyzed for 2h to obtain an intermediate product;
[0056] (6) The intermediate product obtained in step (5) and sulfur powder are sulfurized in an argon atmosphere at a mass ratio of 1:4 at 2°C / min -1 The temperature was raised to 400°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0057] Example 2
[0058] (1) Take 1 mmol of nickel chloride and 3 mmol of hexamethylenetetramine and add them into a ball mill;
[0059] (2) Add 20 g of agate balls with a diameter of 10 mm into the ball mill;
[0060] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 7 hours at a rotation speed of 300 rpm. After the milling is completed, a mixed product is obtained.
[0061] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged with deionized water for multiple times to obtain a Ni-HMT precursor.
[0062] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under argon atmosphere protection and heated at 3 °C min -1 The temperature was raised to 500°C at a heating rate for 3 h to obtain an intermediate product;
[0063] (6) The intermediate product obtained in step (5) and L-cysteine are sulfurized in an argon atmosphere at a mass ratio of 1:5 at 2°C / min -1The temperature was raised to 500°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0064] Example 3
[0065] (1) Add 2 mmol of nickel acetate and 2 mmol of hexamethylenetetramine into a ball mill;
[0066] (2) Add 40 g of agate balls with a diameter of 10 mm into the ball mill;
[0067] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 6 h at a rotation speed of 500 rpm. After the milling is completed, a mixed product is obtained.
[0068] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with ethylene glycol to obtain a Ni-HMT precursor.
[0069] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under argon atmosphere protection and heated at 3 °C min -1 The temperature was raised to 500°C at a heating rate for 3 h to obtain an intermediate product;
[0070] (6) The intermediate product obtained in step (5) is sulfurized with thiourea in a mass ratio of 1:6 under an argon atmosphere at 2°C / min -1 The temperature was raised to 300°C at a heating rate and sulfurized for 2 hours to obtain a NiS2 / nitrogen-doped carbon composite material.
[0071] Example 4
[0072] (1) 1 mmol of nickel sulfate and 2.5 mmol of hexamethylenetetramine were added to a ball mill;
[0073] (2) Add 40 g of agate balls with a diameter of 10 mm into the ball mill;
[0074] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 8 h at a rotation speed of 300 rpm. After the milling is completed, a mixed product is obtained.
[0075] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with N,N-dimethylformamide to obtain a Ni-HMT precursor.
[0076] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under nitrogen atmosphere at 3 °C min -1 The temperature was raised to 700℃ and pyrolyzed for 2h to obtain an intermediate product;
[0077] (6) The intermediate product obtained in step (5) and sulfur powder are sulfurized in an argon atmosphere at a mass ratio of 1:4 at 3 °C min -1 The temperature was raised to 500°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0078] Example 5
[0079] (1) Add 2.5 mmol nickel nitrate and 1 mmol hexamethylenetetramine into a ball mill;
[0080] (2) Add 20 g of agate balls with a diameter of 10 mm into the ball mill;
[0081] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 4 h at a rotation speed of 400 rpm. After the milling is completed, a mixed product is obtained.
[0082] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with deionized water and anhydrous ethanol to obtain a Ni-HMT precursor.
[0083] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under nitrogen atmosphere at 2 °C min -1 The temperature was raised to 700℃ and pyrolyzed for 2h to obtain an intermediate product;
[0084] (6) The intermediate product obtained in step (5) and sulfur powder are sulfurized in an argon atmosphere at a mass ratio of 1:6 at 2°C / min -1 The temperature was raised to 400°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0085] Example 6
[0086] (1) Add 2 mmol of nickel nitrate and 2 mmol of hexamethylenetetramine into a ball mill;
[0087] (2) Add 24 g of large (20 mm diameter) agate ball milling beads and 6 g of small (5 mm diameter) agate ball milling beads into a ball mill;
[0088] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 2 h at a rotation speed of 500 rpm;
[0089] (4) After the ball milling in step (3) is completed, the ball milling beads in step (3) are replaced with 9 g of large ball milling beads (diameter 20 mm) and 21 g of small ball milling beads (diameter 5 mm), and the ball milling is continued for 2 h at a speed of 300 rpm;
[0090] (5) After the ball milling in step (4) is completed, the ball mill is taken out, 8 ml of ethanol solution is added, and the ball mill is placed in the ball mill again for ball milling for 1 hour at a ball milling speed of 200 rpm. After the ball milling is completed, a mixed product is obtained;
[0091] (6) taking out the mixed product obtained in step (5), washing it with anhydrous ethanol and centrifuging it for multiple times to obtain a Ni-HMT precursor;
[0092] (7) The Ni-HMT precursor obtained in step (6) was pyrolyzed under argon atmosphere protection and heated at 2 °C min -1 The temperature was raised to 600℃ and pyrolyzed for 2h to obtain an intermediate product;
[0093] (7) The intermediate product obtained in step (6) and sulfur powder are sulfurized in an argon atmosphere at a mass ratio of 1:4 at 2°C / min -1 The temperature was raised to 400°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0094] Comparative Example 1
[0095] (1) 1 mmol of nickel sulfate and 2.5 mmol of hexamethylenetetramine were added to a ball mill;
[0096] (2) Add 40 g of agate balls with a diameter of 10 mm into the ball mill;
[0097] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 8 h at a rotation speed of 300 rpm. After the milling is completed, a mixed product is obtained.
[0098] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with N,N-dimethylformamide to obtain a Ni-HMT precursor.
[0099] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under nitrogen atmosphere at 3 °C min -1 The temperature was raised to 700℃ and pyrolyzed for 2h to obtain an intermediate product;
[0100] (6) The intermediate product obtained in step (5) and sulfur powder are vulcanized in a nitrogen atmosphere at a mass ratio of 1:6 at 2°C / min-1 The temperature was raised to 400°C at a heating rate and sulfurized for 3 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0101] Comparative Example 2
[0102] (1) Take 1 mmol of nickel chloride and 3 mmol of hexamethylenetetramine and add them into a ball mill;
[0103] (2) Add 20 g of agate balls with a diameter of 10 mm into the ball mill;
[0104] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 7 hours at a rotation speed of 300 rpm. After the milling is completed, a mixed product is obtained.
[0105] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with ethylene glycol to obtain a Ni-HMT precursor.
[0106] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under nitrogen atmosphere at 3 °C min -1 The temperature was raised to 700℃ and pyrolyzed for 2h to obtain an intermediate product;
[0107] (6) The intermediate product obtained in step (5) and L-cysteine are sulfurized in a nitrogen atmosphere at a mass ratio of 1:5 at 2°C / min -1 The temperature was raised to 500°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0108] Comparative Example 3
[0109] (1) 2 mmol nickel nitrate and 3 mmol hexamethylenetetramine were added into a ball mill;
[0110] (2) Add 20 g of agate balls with a diameter of 10 mm into the ball mill;
[0111] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 4 h at a rotation speed of 400 rpm. After the milling is completed, a mixed product is obtained.
[0112] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with anhydrous ethanol to obtain a Ni-HMT precursor.
[0113] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under nitrogen atmosphere at 2 °C min -1The heating rate was raised to 700℃ for 2h to obtain a pyrolysis intermediate product;
[0114] (6) The intermediate product obtained in step (5) and sulfur powder are vulcanized in a nitrogen atmosphere at a mass ratio of 1:6 at 2°C / min -1 The temperature was raised to 400°C at a heating rate and sulfurized for 2 hours to obtain NiS2 / nitrogen-doped carbon composite materials.
[0115] Comparative Example 4
[0116] (1) Add 2 mmol of nickel acetate and 2 mmol of hexamethylenetetramine into a ball mill;
[0117] (2) Add 30 g of agate balls with a diameter of 10 mm into the ball mill;
[0118] (3) placing the ball mill described in (2) into a planetary ball mill and assembling the mill appropriately, and milling the mill for 6 h at a rotation speed of 500 rpm. After the milling is completed, a mixed product is obtained.
[0119] (4) The mixed product obtained in step (3) is taken out, and washed and centrifuged multiple times with anhydrous ethanol to obtain a Ni-HMT precursor.
[0120] (5) The Ni-HMT precursor obtained in step (4) was pyrolyzed under nitrogen atmosphere at 3 °C min -1 The temperature was raised to 500°C at a heating rate for 3 h to obtain an intermediate product;
[0121] (6) The intermediate product obtained in step (5) and thiourea are sulfurized in a nitrogen atmosphere at a mass ratio of 1:6 at 2°C / min. -1 The temperature was raised to 300°C at a heating rate and sulfurized for 2 hours to obtain a NiS2 / nitrogen-doped carbon composite material.
[0122] Performance Testing
[0123] The final product obtained in each embodiment and comparative example is mixed with a conductive agent (Super P) and a binder (PVDF) in a mass ratio of 7:2:1. The product is first mixed with the conductive agent in a fixed ratio, and after multiple grindings and uniform mixing, a fixed ratio of PVDF is added and a suitable amount of solvent N-methylpyrrolidone (NMP) is used to make a homogeneous slurry, and then evenly coated on the current collector (copper foil). After drying at a constant temperature of 60°C for 12 hours, a 12mm pole piece is punched out by a cutting machine as an electrode. A glass fiber membrane is used as a diaphragm, a metal sodium sheet is used as a counter electrode, and 1.0 mol·L -1The half-cell was assembled with NaPF6 as the solute and diethylene glycol dimethyl ether as the solvent electrolyte. The battery was assembled in a glove box filled with argon gas, and the operation was completed from bottom to top in the order of positive electrode shell, prepared electrode, diaphragm, electrolyte, metal sodium sheet, nickel foam and negative electrode shell. The assembled sodium ion half-cell was left to stand for 24 hours, and then the electrochemical test was carried out under constant temperature conditions.
[0124] Figure 1 This is the XRD spectrum of the Ni-HMT precursor obtained after ball milling and washing in Example 1. It can be seen that the precursor has good crystallinity.
[0125] Figure 2 This is the SEM picture of the sample of Example 2 after high-temperature heat treatment. It can be seen that the intermediate product presents a needle-punctured morphology with a length of about 500 nm.
[0126] Figure 3 This is the SEM image of Example 1 after subsequent sulfurization treatment. In the image, some spherical particles can be seen distributed on the carbon skeleton. The particles are NiS2 particles with a particle size between 200 and 400 nm. The particles are relatively evenly distributed on the surface of the carbon skeleton, and there is a certain amount of agglomeration between the materials.
[0127] Figure 4 This is the SEM image of Example 6 after subsequent sulfurization treatment. In the image, an obvious carbon skeleton can be seen, and there are some spherical particles distributed on the carbon skeleton. The particles are NiS2 particles with a particle size between 100 and 200 nm. The particles are relatively evenly distributed on the surface of the carbon skeleton, and there is no obvious agglomeration between the materials.
[0128] Figure 5 This is the XRD diagram of the final product of Example 4. The results in the figure show that the final product is cubic NiS2 (PDF#04-004-6507), and a not very obvious broad diffraction peak appears near 25°. This peak belongs to amorphous carbon. Since the product peak intensity of NiS2 is very high, the peak intensity of amorphous carbon is not very obvious, which proves the successful preparation of NiS2 / nitrogen-doped carbon composite materials.
[0129] Figure 6 For Example 1, at a current density of 1A -1 The cycle performance diagram shows that after 100 cycles at this current density, the capacity of the half-battery remains at 630 mAh g -1 This indicates that this material has good cycle stability.
[0130] Figure 7 The rate performance diagram of Example 1 at different current densities is shown in Figure 1. -1 , 0.2Ag -1, 0.5Ag -1 , 1Ag -1 , 2Ag -1 , 5A g -1 and return to the initial 0.1A g -1 The specific capacity at the current density of 766.3 mAh g -1 、750.6mAh g -1 、681.2mAh g -1 、651.6mAh g -1 , 564.8mAh g -1 , 432.6mAh g -1 and 768.7mAh g -1 The material has a high capacity and can return to its initial capacity after large current cycles, indicating that the material has high stability and excellent rate performance.
[0131] The capacities at the 100th cycle and the first cycle coulombic efficiencies of Examples 1 to 6 and Comparative Examples 1 to 4 are shown in Table 1.
[0132] Table 1
[0133] <![CDATA[Capacity at the 100th cycle (mAh / g -1 )]]> First cycle coulomb efficiency (%) Example 1 642.8 85.4 Example 2 550.4 84.2 Example 3 533.8 78.8 Example 4 492.7 80.1 Example 5 474.6 73.5 Example 6 670.3 86.1 Comparative Example 1 424.6 72.1 Comparative Example 2 441.1 77.8 Comparative Example 3 518.3 80.8 Comparative Example 4 468.2 76.7
[0134] *Current density is 1A -1 (voltage window is 0.01~3V) test.
[0135] Table 1 summarizes the examples and comparative examples in 1Ag -1The capacity of the half-cell at 100 cycles and the coulombic efficiency of the first cycle at a current density of . The capacity of Example 1 at 100 cycles is significantly higher and the coulombic efficiency is higher than that of Examples 2, 3, and 4. This is because after different nickel salts combine with organic ligands to form coordination compounds, the anions in the nickel salts have different effects on the coordination compound derivatives in the subsequent treatment. Nitrates can better improve the performance of the material, while sulfates have the least effect on the overall material performance. Comparing Example 6 with Example 1, it can be seen that different ball milling processes will have a certain impact on the performance of the product. In Example 6 using Scheme B, multi-step ball milling and the addition of dispersing grinding aids reduce the agglomeration between the materials, and the nanoparticles of the final sample are smaller and more evenly dispersed. Compared with Comparative Example 3, Example 5 shows that the ratio of nickel salt to the organic ligand hexamethylenetetramine will also have a significant impact on the performance of the material. If the amount of organic ligands is too high, after subsequent heat treatment and vulcanization, the carbon skeleton content inside the material increases, which can increase the stability of the material, but the material will lose some capacity; if the content of organic ligands is less, then after subsequent treatment, the obtained carbon skeleton content will be relatively small, and the confinement effect of the carbon skeleton will be weakened. At this time, the volume expansion of the material during the cycle will become obvious, and the stability of the material structure will be significantly reduced; Comparative Example 4 is compared with Example 3. During the ball milling process, the total mass ratio of the nickel salt and the organic ligand to the total mass ratio of the ball milling beads will affect the performance of the final material. If the mass of the ball milling beads added during the ball milling process is less, the material will not be completely crushed during the ball milling process. In the subsequent reaction process, the large granular material will be coated by the crushed powder particles, and a good reaction cannot occur. There are incomplete parts, which cause waste of raw materials during the washing process. At the same time, larger particles will produce larger particles after subsequent heat treatment, and the performance will be reduced to a certain extent.
[0136] Table 2
[0137]
[0138] *Test voltage window is 0.01~3V
[0139] Table 2 shows the capacity of each embodiment and comparative example at different current densities. Comparing embodiments 1 and 6 with embodiments 2, 3, and 4, the capacity of some materials can return to the initial capacity when returning to the initial current after passing through different currents, proving that such materials have good repeatability and recyclability. Comparing embodiment 6 with embodiment 1, the finer particles make the material perform better at higher current densities, because when the current sweep rate is large, the smaller particles have a larger response area, which can better reflect the performance advantage than large particles; comparing embodiment 4 with comparative example 1, the final vulcanization heating rate and the ratio of the intermediate product Ni / NC to sulfur powder will affect the final performance of the material. If the heating rate is too fast, the ratio of sulfur powder is too high, and the gas velocity is too fast, the intermediate product cannot be completely vulcanized, and the sulfur powder does not react but exists in the carbon skeleton of the sample in the form of physical adsorption. Incomplete vulcanization makes the material Performance is reduced, and the physical adsorption of sulfur powder causes the material to be directly overcharged at a high rate; it can be seen from Example 2 and Comparative Example 2 that different pyrolysis temperatures will affect the final electrochemical performance of the material and the structure and distribution of the product. A reasonable pyrolysis temperature can obtain a material with an ideal structure, and at the same time adjust the ratio of amorphous carbon and graphite carbon inside the material to obtain the best electrochemical performance; but if the pyrolysis temperature is too high, it is very likely to destroy the structure of the material and fail to obtain the ideal state; if the pyrolysis temperature is too low, the internal decomposition of the material is not complete, resulting in unevenness inside the material, the presence of multiple components and structures, and finally affecting the performance of the material. Therefore, in the process of preparing battery materials, it is necessary to accurately control the ratio of nickel salt to ligand hexamethylenetetramine and the pyrolysis temperature to ensure that the best battery performance can be obtained.
[0140] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0141] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material, characterized in that The following steps are involved: (1) placing nickel salt and organic ligand hexamethylenetetramine in a ball mill, and obtaining a coordination compound Ni-HMT precursor by mechanochemical reaction and washing, wherein the molar ratio of the nickel salt to the hexamethylenetetramine is (1-3): (0.5-3); (2) pyrolyzing the Ni-HMT precursor under an inert protective atmosphere to obtain an intermediate product; the pyrolysis temperature is 400 to 800°C, and the heating rate is 1 to 8°C min -1 , the insulation time is 1 to 5 hours; (3) heat-treating the intermediate product and the sulfur source under an inert protective atmosphere to obtain a NiS2 / nitrogen-doped carbon composite material having a nitrogen-doped carbon skeleton and uniformly distributed NiS2 particles; the mass ratio of the intermediate product to the sulfur source is 1:(2-8).
2. The preparation method according to claim 1, characterized in that: In step (1), The mass ratio of the total mass of the nickel salt and the organic ligand hexamethylenetetramine to the ball milling beads is 1:(10-40); The diameter of the ball milling beads is 8 to 12 mm; The mechanochemical reaction time is 1 to 8 hours, and the rotation speed is 300 to 600 rpm.
3. The preparation method according to claim 1, characterized in that: In step (1), the mechanochemical reaction includes the following stages: The first stage: mainly using large ball milling beads to crush the material particles; the mass ratio of the total mass of nickel salt and organic ligand hexamethylenetetramine to the mass ratio of ball milling beads is 1: (10-40), the diameter of large ball milling beads is 15-25 mm, the diameter of small ball milling beads is 3-7 mm, the mass ratio of large and small ball milling beads is (7.5:2.5)-(8.5:1.5), the ball milling time is 1-2 hours, and the rotation speed is 400-600 rpm; The second stage: without changing the ball-to-material ratio, some large ball milling beads are replaced with small ball milling beads of the same mass, the crushed raw material particles are mixed and refined, and the reaction is promoted; the mass ratio of large and small ball milling beads is (2.5:7.5) to (3.5:6.5), the ball milling time is 2 to 4 hours, and the rotation speed is 300 to 500 rpm; The third stage: adding a grinding aid and dispersant, continuing ball milling, taking out after the reaction is completed, washing with a detergent, and centrifuging to obtain a coordination compound Ni-HMT precursor; the grinding aid and dispersant are isopropanol, anhydrous ethanol or ethylene glycol, the ball milling speed is 200-400rpm, and the ball milling time is 1-3h.
4. The preparation method according to claim 1, characterized in that: In step (1), the nickel salt is any one of nickel chloride, nickel acetate, nickel sulfate or nickel nitrate.
5. The preparation method according to claim 1, characterized in that: In step (1), the washing detergent is anhydrous ethanol, ethylene glycol, deionized water or N,N-dimethylformamide.
6. The preparation method according to claim 1, characterized in that: In step (2), the protective atmosphere is argon or nitrogen.
7. The preparation method according to claim 1, characterized in that: In step (3), the sulfur source is sulfur powder, L-cysteine, thiourea or thioacetamide.
8. The preparation method according to claim 1, characterized in that: In step (3), the heat treatment temperature is 200-600° C.; the inert protective atmosphere is nitrogen or argon.
9. The preparation method according to claim 1, characterized in that: In step (3), the carbon skeleton in the NiS2 / nitrogen-doped carbon composite material having a nitrogen-doped carbon skeleton and uniformly distributed NiS2 particles has pores with a pore size of 2 to 8 μm, and the NiS2 particles are confinedly distributed in the nitrogen-doped carbon skeleton with a particle size of 50 to 100 nm.
10. Application of the coordination compound-derived confined NiS2 / nitrogen-doped carbon composite material obtained by the preparation method as described in any one of claims 1 to 9 as a negative electrode material for sodium ion batteries.
Citation Information
Patent Citations
Porous FeS2-nitrogen-doped carbon framework material as well as preparation method and application thereof
CN116779815A